Demographic and Geographic Variation in Fatal Drug Overdoses in the United States, 1999–2020. Issue 1 (September 2022) - Monnat, Shannon M.
The U.S. drug overdose crisis has been described as a national disaster that has affected all communities. But overdose rates are higher among some subpopulations and in some places than they are in others. This article describes demographic (sex, racial/ethnic, age) and geographic variation in fatal drug overdose rates in the United States from 1999 to 2020. Across most of that timespan, rates were highest among young and middle-age (25–54 years) White and American Indian males and middle-age and older (45+ years) Black males. Rates have been consistently high in Appalachia, but the crisis has spread to several other regions in recent years, and rates are high across the urban-rural continuum. Opioids have been the main contributor, but overdoses involving cocaine and psychostimulants have also increased dramatically in recent years, demonstrating that our problem is bigger than opioids. Evidence suggests that supply-side interventions are unlikely to be effective in reducing overdoses. I argue that the U.S. should invest in policies that address the upstream structural drivers of the crisis.